Prediction of existing reflective cracking potential of flexible pavements - Pais, Jorge C. (2000)
"Reflective cracking in pavements : research in practice" contains the Proceedings of the 4th International RILEM Conference on Reflective Cracking in Pavements (Proceedings PRO11).